2014
DOI: 10.12720/ijeee.2.1.8-14
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity Analysis of Characteristic Parameters of Railway Electric Traction System

Abstract: The modal analysis, which decouples the contact wire and rail track conductors, is used to develop an integrated model of single rail track and contact wire. The characteristic impedance and propagation constant matrices of integrated model have been computed. The authors have studied effects of various parameters of interest on characteristic impedance and propagation constant using sensitivity analysis. The sensitivity functions of series impedance and shunt admittance related to contact wire and catenary ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The sensitivity of these parameters with respect to frequency is determined in frequency domain and the results are discretised to evaluate the normalized sensitivity as given in Table 4. These sensitivity functions in z-domain are then compared with the sensitivity functions of analog model [1]. From the Table 3, it is observed that as the sampling time is reduced, more time instants are required for the digital model to approach that of analog model [1], which is the expected behavior.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The sensitivity of these parameters with respect to frequency is determined in frequency domain and the results are discretised to evaluate the normalized sensitivity as given in Table 4. These sensitivity functions in z-domain are then compared with the sensitivity functions of analog model [1]. From the Table 3, it is observed that as the sampling time is reduced, more time instants are required for the digital model to approach that of analog model [1], which is the expected behavior.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…These sensitivity functions in z-domain are then compared with the sensitivity functions of analog model [1]. From the Table 3, it is observed that as the sampling time is reduced, more time instants are required for the digital model to approach that of analog model [1], which is the expected behavior. From the Table 4, it is found that the digital sensitivity of characteristic impedance with respect to frequency is approaching the analog sensitivity at smaller sampling time.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In many countries, 25kV, 50Hz single phase ac supply is fed to the electric loco which is stepped down to different voltage levels by the loco transformer for various functions [18]. One of the winding of loco transformer is used to feed the traction drive through converter-inverter system.…”
Section: Railway Electric Traction Systemmentioning
confidence: 99%